Reliability and validity of the Japanese version of the Ocular Surface Disease Index for dry eye disease - Akira Murakami; Yuichi Okumura; Takenori Inomata; Masao Iwagami; Atsuko Eguchi; Shuko Nojiri; Hiroyuki Kobayashi; Akie Midorikawa-Inomata; Masahiro Nakamura; Keiichi Fujimoto; Nanami Iwata; Hitomi Hasegawa; et al. (BMJ Open)
Objectives The Ocular Surface Disease Index (OSDI) questionnaire is widely used to evaluate subjective symptoms of dry eye disease (DED) as a primary diagnostic criterion. This study aimed to develop a Japanese version of the OSDI (J-OSDI) and assess its reliability and validity.Design and setting Hospital-based cross-sectional observational study.Participants A total of 209 patients recruited from the Department of Ophthalmology at Juntendo University Hospital.Methods We translated and culturally adapted the OSDI into Japanese. The J-OSDI was then assessed for internal consistency, reliability and validity. We also evaluated the optimal cut-off value to suspect DED using an area under the receiver operating characteristic curve (AUC) analysis.Primary outcome measures Internal consistency, test–retest reliability and discriminant validity of the J-OSDI as well as the optimal cut-off value to suspect DED.Results Of the participants, 152 had DED and 57 did not. The J-OSDI total score showed good internal consistency (Cronbach's alpha=0.884), test–retest reliability (interclass correlation coefficient=0.910) and discriminant validity by known-group comparisons (non-DED, 19.4±16.0; DED, 37.7±22.2; p<0.001). Factor validity was used to confirm three subscales within the J-OSDI according to the original version of the questionnaire. Concurrent validity was assessed by Pearson correlation analysis, and the J-OSDI total score showed a strong positive correlation with the Dry Eye-Related Quality-of-Life Score (γ=0.829). The optimal cut-off value of the J-OSDI total score was 36.3 (AUC=0.744).Conclusions The J-OSDI was developed and validated in terms of reliability and validity as an effective tool for DED assessment and monitoring in the Japanese population.